2020
DOI: 10.14712/23363177.2020.10
|View full text |Cite
|
Sign up to set email alerts
|

Gender- and SES-Specific Disparities in Shadow Education: Compensation for Boys, Status Upgrade for Girls? Evidence From the German LifE Study

Abstract: In the present article, we draw on social reproduction theories to explain the increase in the use of "shadow education" (SE) in Germany over the last two decades as a status-based, gender-specific investment strategy of families. Thus, we ask whether investing in private tutoring for both girls and boys alike serves to maintain or improve their status position, or whether gender-specific investment strategies exist. Our hypotheses are quantitatively tested by means of logistic regression using data of the 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…However, detailed analyses further showed that it is not the economic resources of a family that determine whether SE is used, but that cultural and educational resources stronger influence SE access. In fact, these results coincide with the results of national studies, which indicate that economic resources play a greater role for less educated groups and that economically less advantaged strata make even more use of SE to support their below-average-performing children in Germany (Entrich and Lauterbach, 2019, 2020).…”
Section: Discussionsupporting
confidence: 83%
“…However, detailed analyses further showed that it is not the economic resources of a family that determine whether SE is used, but that cultural and educational resources stronger influence SE access. In fact, these results coincide with the results of national studies, which indicate that economic resources play a greater role for less educated groups and that economically less advantaged strata make even more use of SE to support their below-average-performing children in Germany (Entrich and Lauterbach, 2019, 2020).…”
Section: Discussionsupporting
confidence: 83%
“…The work on the increase in the use of shadow education in Germany over the last two decades describes it as a gender specific phenomenon contrasting generally accepted beliefs that it promotes social inequity. It is largely independent of social origin but is mainly used by boys from non-academic high-income families while girls remain “unaffected by social origin entirely” (Entrich and Lauterbach, 2020). The authors’ later research states that despite dissimilarities of shadow education in different parts of the world and systems of education, it “always feeds into the broader institutionalization of education”, and moreover it “might occupy a key role in maintaining vertical and horizontal inequalities in educational attainment in schooled societies” (Entrich and Lauterbach, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although there is substantial research evidence on shadow education from these countries (e.g. Jansen, Elffers, and Volman 2020;Feistritzer 2020;Entrich and Lauterbach 2020;Kubánová 2006;Győri 2020), it has not directly addressed the question of differences in shadow education features between academic or regular-track students. Where differences are reflected upon, they are limited to comparisons of the scale of the phenomenon among students of different tracks/school types (e.g.…”
Section: Introductionmentioning
confidence: 99%